Response of total renewable energy consumption to environmental technologies and policy uncertainties: A time–frequency analysis - Uzun, Berna; Adebayo, Tomiwa Sunday; Henni, Mohamed Djafar; Olanrewaju, Victoria Olushola (Edelweiss Applied Science and Technology, 2026)
Renewable energy transition in the United States unfolds in a landscape shaped not only by technological progress but also by policy-related uncertainty. Using monthly U.S. data from 01/04 /2005 to 01/11/2025, this study examines how climate policy uncertainty (CPU), monetary policy uncertainty (MP), and environmental technologies (ET) influence total renewable energy consumption (TREC) through advanced time–frequency techniques. In doing so, the study employs wavelet coherence (WTC), partial wavelet coherence (PWC), and multiple wavelet coherence (MWC) techniques. The results show that the TREC nexus is strongly time- and frequency-dependent. Baseline WTC indicates that CPU and MP are linked with TREC mainly in the short and medium run, whereas ET exhibits a more persistent medium- and long-run relationship. PWC confirms that the TREC–CPU association remains largely short-run after controlling for ET and MP, while the TREC–ET relationship continues to dominate over medium- and long-term horizons after accounting for CPU and MP. MWC further reveals that TREC is shaped not only by individual determinants but also by the joint influence of uncertainty and technology, especially at medium frequencies. We formulate policies based on these findings.